P878 Country is the main determinant of differences in nutritional therapy practices across Europe: Results of the Y-ECCO ClinCom Survey 2022. (30th January 2023) - Selin, K A; Andersson, S; Bilén, K; Strid, H; Björk, J; Bresso, F; Hedin, C
Abstract: Background: Diet is known to affect inflammatory bowel disease (IBD), but the optimal nutritional therapy during a severe flare is uncertain. The goal of this study was to describe variation in nutritional practices across Europe, between professions, types of hospitals and healthcare systems, as well as between ulcerative colitis (UC) and Crohn's disease (CD). Methods: A novel questionnaire comprising 17 questions, of which 5 concerning demographic data, was distributed digitally in the ECCO Congress 2022 and via the ECCO country representatives. In the comparisons of categories (e.g., countries), only categories with at least 25 responses were considered, and Chi-squared test was used. Results: The survey was completed by 313 participants. Table 1 summarises their main characteristics. Physicians and dietitians were most commonly responsible for determining nutritional therapy for IBD inpatients (Table 2). The commonest form of nutritional therapy was oral nutritional supplements (ONS) on top of easy to digest food. Total parenteral nutrition (TPN) was used by 10% of respondents for UC patients and 7% for CD. Almost a quarter of respondents reported less than 25% of patients being assessed by a dietitian in the first 3 days of a flare. Energy intake, stool frequency and inflammatory biomarkers were the commonest factors to determine when to change nutritional therapy. No specific nutritional screening tool was used by 45% of respondents. There was significant variation between different European countries and healthcare professions for all the outcomes measured (p<0.050). However, in 7 of total 12 questions the variation between professions was only caused by variation in selecting the "I don't know" alternative. When countries were grouped by healthcare index (HI), countries with high HI showed higher proportion using ONS on top of easy to digest food in CD (p=0.008), being more likely to use a specific nutritional screening tool for assessment (p<0.001) and using more approximate nutritional monitoring in UC instead of reporting all intake (p=0.002). Moreover, nutritional therapy management did not vary according to hospital type (university versus general), apart from criteria of changing nutritional therapy in CD (p=0.021) and monitoring intake in UC (p=0.046). During the first three days of a severe flare, a diet consisting exclusively of ONS was significantly more frequently used for CD than UC (p=0.018, Figure 1). Otherwise, similar nutritional therapy strategies were reported for CD and UC including using TPN to a similar extent. Conclusion: Country is the main determinant of differences in nutritional practice across Europe. Diet consisting exclusively of ONS is more common during a flare of CD than UC.